Virtual simulation analysis and verification of seed-filling mechanism for dipper hill-drop precision direct rice seeder - Jinwu, Wang; Wenqi, Zhou; Liquan, Tian; Shuwei, Li; Zhao, Zhang (International Journal of Agricultural and Biological Engineering, 2017)
In order to improve the seeder’ seed-filling ability of the dipper hill-drop precision direct rice seeder, and to meet the mechanization requirement of high speed operation, the self-designed seeder was taken as the objective to explore its seed-filling mechanism and the movement status of rice seed in seed box from the perspective of mechanics. The force models of seed-filling process by dipper were established, and the influential regularity of its rotation speed to compressive resistance of seed population was analyzed as well. The image processing Module-Clipping of discrete element simulation software EDEM was used in the virtual simulation analysis for the process of the seed filling into the dipper, and the velocity relation curve and the force changing curve between rotation speed and seeds were obtained. According to the virtual experiment, the composite filling force of seeds, i.e. the qualified rate on filled rice seed amounts was the largest when rotation speed was at 40 r/min. The performance test bed of seeder was used to verify the simulation results, in which the qualified rate on scooped rice seed amounts was taken as the index, and six rotation speeds of seed-filling dipper were also selected for analysis of seed-filling ability of the device. The results are as follows: with the increase of working speed, the qualified rate on filled rice seed amounts fluctuated with a trend of cosine curve, the largest value was 94.16% occurred when the rotation speed of seed-filling dipper was at 40 r/min. The variation trend of simulation value was approximately consistent with that of verification value. The study can provide a reference for the research and development of mechanical seeder. Keywords: precision direct rice seeding, rice seed, dipper seeder, seed-filling performance, EDEM, force model DOI: 10.25165/j.ijabe.20171006.2981 Citation: Wang J W, Zhou W Q, Tian L Q, Li S W, Zhang Z. Virtual simulation analysis and verification of seed-filling mechanism for dipper hill-drop precision direct rice seeder. Int J Agric & Biol Eng, 2017; 10(6): 77–85.